The Issue of Artistic Image of Nature and Method In The Works Of Isajan Sultan (On The Example Of “The Missing Motherland”) - Davronova Shohsanam G'aybulloevna (Indonesian Journal of Innovation Studies, 2022)
The article describes the views of the writer Isajon Sultan on the art of creating an artistic image, his methodological research on the example of the story "Ona yurt sog’inchi".